Analysis of Caring Thinking's Quiddity Based on Its Dimensions, Types, and Nature - Hajar Kouhi Esfahani; yahya ghaedi; saeed zarghami hamrah; Sussan Keshavarz (Shahid Chamran University of Ahvaz, 2022)
IntroductionCaring thinking is the third category of thinking based on Lipman's classification that integrates human emotions in intellectual affairs. Caring thinking conjugates 3H; Head, Heart, and Hand as symbols of contemplation, kindness, and behavior. Research QuestionThis new category of thinking has not been effectively considered, especially in philosophical view. Therefore, the pros and cons of caring thinking and its implementation should be assessed and identified from a philosophical perspective. So the goal of this research is the analysis of caring thinking's quiddity based on its dimensions, types, and nature and responding to challenges in these areas. MethodIn this paper, we elaborate quiddity of caring thinking by applying the concept analysis method. The basic purpose of our methodology is to consider concepts of different types of caring thinking that results in distinguishing characteristics of each type. Discussion and ResultsWe investigate: (1) The interference and differentiation of 5 types of caring thinking (Appreciative / Valuational, Emotional, Active, Normative, Empathetic ), the interaction between these types, their relations to Bloom's taxonomy of educational approaches, and their individual and social effectiveness scope,(2) Dimensions of caring thinking based on how it affects the thinker (subject), the target (object), and the target's manner of thinking, (3) The nature of caring thinking that shows emotional thinking as the start point which consequently results in ethical values, motivations, and actions. Finally, we introduce a four steps implementation of caring thinking that demonstrates its life cycle in a dynamic and self-rectifying society:(1) To pay attention and care to others including living and inanimate creatures as a result of Valuational, Empathetic, and Emotional thinking types,(2) To accredit and respect the rights of others, because of being involved in Emotional and Normative thinking,(3) To apply social, ethical, and biological rights of others in personal decision making and activities as a consequence of the usage of Active thinking,(4) Re-evaluate and revision the previous steps by assessing conditions using the Valuational and Normative thinking types.